Agronomic potential, pest resistance, and fruit quality in BC1F3 dwarf round tomato populations - Resende Finzi, Rafael; Mascarenhas Maciel, Gabriel; Silva Siquieroli , Ana Carolina; Soares de Oliveira, Camila; Miranda Peixoto , Joicy Vitória; Alves Ribeiro , Ana Luisa (Comunicata Scientiae, 2022)
Combining broad pest resistance, high yield, and nutritional quality of fruit in the same hybrid is a challenge for round tomato breeders. Thus, development of a dwarf round tomato line for obtaining hybrids may be an excellent alternative for achieving such objectives. The aim of this study was to evaluate the agronomic potential, fruit quality, and pest resistance of BC1F3 dwarf round tomato populations. We evaluated 13 treatments and 4 replications. Treatments consisted of 10 BC1F3 dwarf populations originating from self-fertilization of dwarf populations selected in BC1F2, plus both parents (recurrent and donor) and a commercial hybrid. The traits evaluated were yield, number of fruit, mean weight, number of locules, shape, pulp thickness, longitudinal and transverse diameter of the fruit, precocity index, and soluble solids, β-carotene, lycopene, and acylsugar content. The data were analyzed through the means test. In general, there was an increase of up to 1035% in average fruit weight of the dwarf populations in relation to the donor parent. In addition, some dwarf populations had fruit with 49% more lycopene compared to the commercial hybrid, as well as greater acylsugar content in the leaves (273%). The UFU-DW22 dwarf population stood out with good agronomic potential, higher lycopene content in the fruit, and high acylsugar content, which provides pest resistance. To continue this research, a second backcross is suggested in order to obtain lines and, posteriorly, hybrids with round fruits and compact plants, pest resistance and nutritional quality of fruit.